2019
DOI: 10.2174/1381612825666190117102111
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Non-alcoholic Fatty Liver Disease (NAFLD): Current Concepts

Abstract: Nonalcoholic fatty liver disease (NAFLD) ranges from simple hepatic steatosis to non-alcoholic steatohepatitis (NASH) and cirrhosis. The majority of NAFLD patients do not progress to NASH and their morbidity risk is low. However, clinical and economic burden of the disease is considerable since the prevalence of the disease is estimated as high as 25% of the general population. Liver biopsy remains the current gold standard for diagnosis, despite limitations regarding sampling variability, invasive nature, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 0 publications
3
115
0
2
Order By: Relevance
“…Exenatide is not widely investigated in patients with NAFLD and T2DM. Limited studies showed promising effects of exenatide on NAFLD [10,27]. We showed in our trial that AST, ALT and GGT levels decreased with exenatide treatment, and we also showed that the liver craniocaudal diameter decreased with exenatide treatment significantly.…”
Section: Discussionsupporting
confidence: 64%
“…Exenatide is not widely investigated in patients with NAFLD and T2DM. Limited studies showed promising effects of exenatide on NAFLD [10,27]. We showed in our trial that AST, ALT and GGT levels decreased with exenatide treatment, and we also showed that the liver craniocaudal diameter decreased with exenatide treatment significantly.…”
Section: Discussionsupporting
confidence: 64%
“…25 Several non-invasive imaging methods have been developed to evaluate the degree of hepatic steatosis. Ultrasonography is a screening technique that typically shows a diffuse increase in echogenicity in fatty liver; 26 it is not as specific or sensitive compared to other imaging techniques especially in morbidly obese patients. 27 Transient elastography detects and quantifies steatosis and fibrosis by measuring ultrasound signals emitted from the FibroScan probe.…”
Section: Diagnosis Of Nafld and Modes Of Evaluationmentioning
confidence: 99%
“…27 Transient elastography detects and quantifies steatosis and fibrosis by measuring ultrasound signals emitted from the FibroScan probe. 26 Magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS) are considered the most accurate imaging modalities for estimation of intrahepatic fat content. 15,16 Scoring systems have also been developed for estimation of the degree of liver fibrosis.…”
Section: Diagnosis Of Nafld and Modes Of Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Young modulus, E, is measured in kilopascals (kPa), and it corresponds to the liver stiffness, such that a higher value indicates a stiffer tissue. Liver stiffness range between 1.5 to 75 kPa [ 40 , 41 ] with normal values at around 4.5 to 5.5 kPa in the healthy population [ 35 ]. The equipment displays the median of the measured Young’s modulus, the interquartile range (IQR), the interquartile range/median ratio (IQR/M) after 10 conclusive measurements, and also the success rate of the measurements (SR) [ 31 ].…”
Section: The Main Elastographic Techniquesmentioning
confidence: 99%